A roça como categoria de análise e de afirmação identitária: estudo da relação dinâmica de resistência e garantia do território em situações sociais referidas a quilombolas e indígenas. - Lima, Luís Augusto Pereira (2015)
Developed this dissertation work at first, with the intention to propose an analysis of what I refer as swidden under a category of analysis from social situations investigated with Mata Boi Quilombolas (Monção-MA) and the indigenous people of New Hope Kokama (Manaus - AM). Addition of recurrences to PNCSA publications and theoretical references, cartographic techniques printed an advantage for the construction of maps. In this proposal I considered my own living and experience in swidden and the polissemic perception of the investigated social agents, for this correlated a discussion which argues in favor of the singular resistance of peoples and traditional communities, highlighted the quilombolas fighting for titration of traditionally occupied territory and conflict situations. On the other hand, the indigenous Kokama reorganize their "new" territory due to an eviction "forced". At these events, I observed different realities. Although resistance are connected, economic and social absorbing the dynamics of this category, swidden, also includes a universe that transcends the social relations, in other words, a "territories of reserve". Since the other side of understandings , social and political , is the state and business, ie the government and the market constituting "advances", programs, policies and mega projects that have tried to override the specificities of as many traditional communities and the situations studied. To this, I proposed a representation of the Amazon region, as a "resistance landscape" where traditional peoples and communities are asserting their knowledge and practices forward the “technological changes” connected with the expansion of agribusiness. The study provided arguments and meanings given to the category swidden as part of a dynamic relationship of strength and guaranty of the territory, therefore, an identity statement. Not formulated comparisons, but I affirm that the swidden represent an element to these groups. Considering in Mata Boi, to momentarily stop put swidden, do not open more hand to do it. New Hope Kokama, the swidden is in the center of the community. By entrusting to the swidden, its production and physical and social reproduction, groups gain autonomy, resistance and strategy to continue "putting” swidden. The link of the work with territory and collective identity remains strengthened. This work also revealed aspects, "clearances" of water resources and territories that contribute to future investigations on the swidden as resistance meaning to peoples and traditional communities.